ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI PREDIKSI PERINGKAT OBLIGASI PADA PERUSAHAAN NON-KEUANGAN YANG TERDAFTAR DI BEI PERIODE 2011 – 2013 - Asih '; Emrinaldi Nur DP; Sempaulus Silalahi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The Rate of obligation is very important for the company, because when a company has a good rating, then investors will be attracted to invest. This research purposed to get know about factors that influence the obligation rate of all non-finance company that registered in Indonesia Stoch Exchange and in rated by PT. PEFINDO at 2011-2013 period. Factors that influence the rate of obligation are divided into two factor, 1) the accounting factors consist of company size , leverage, profitability, the company's activity, liquidity, and the growth of the company. 2) non accounting factors consist of maturity, secure and reputation auditor.This research use desain purposive sampling. Sample that use in this research amount 95 obligation which are from 41 non-finance company. Data used in this research was secondary data. The data was obtained from financial report on 2010 – 2012 from companies that listed in Indonesia Stock Exchange and in rated by PT. PEFINDO. Hypothesis tested by logistic regression analysis method. Result of this research shows that variable of company size (4,5%),profitability (4,9%), company activities(4%), maturity(2,3%), auditor reputation (3,3%), liquidity (3,5%), and companies growth (3%) had an positive influence to obligation rate. Meanwhile leverage (90,9%) and secure (73,9%) didn’t have significant influence to obligation rate.Keywords:Bond Rating, Accounting Factors, Non- Accounting Factors